Behaviour of Rubberized Concrete Short Columns Confined by Aramid Fibre Reinforced Polymer Jackets Subjected to Compression - Gabriel Oprişan; Ioana-Sorina Enţuc; Petru Mihai; Ionuţ-Ovidiu Toma; Nicolae Ţăranu; Mihai Budescu; Vlad Munteanu (Advances in Civil Engineering)
The paper presents experimental and numerical investigations on the behaviour of rubberized concrete short columns confined with aramid fibre reinforced polymer (AFRP) subjected to compression. Additionally, the possibilities to substitute fine aggregate with crumb rubber granules, obtained from discarded worn tires, in structural concrete is also assessed. Because replacing traditional concrete aggregates by rubber particles leads to a significant loss in compressive strength, the authors highlight the use of AFRP confinement to partially or fully restore the compressive strength by applying a number of 1, 2, and 3 layers. Analytical models available for confined regular concrete are used to predict the peak stresses and the corresponding peak strains. Some analytical models give accurate results in terms of peak stress while others better approximate the ultimate strain. The full stress-strain curve of rubberized concrete and the experimentally obtained values for the material properties of AFRP are used as input data for the numerical modelling. A good agreement is found between the results obtained for the peak stress and corresponding axial strain from both the numerical simulations and the experimental investigations.